Breastfeeding Behaviour among First Time Mothers Visiting Selected Health Facilities in Ga East District of Greater Accra Region - Nortey, T. (University of Ghana, 2015)
BACKGROUND: Timely breastfeeding initiation is critical to child survival and development. First-time mothers are particularly vulnerable to poor breastfeeding practice. Although studies have been conducted on breastfeeding initiation, first time mothers have not been prioritized. OBJECTIVE: To determine prevalence of timely breastfeeding initiation, and the associated factors of breastfeeding initiation and suboptimal child feeding practices during first six months among first time mothers in Ga East District of Greater Accra. DESIGN: A facility-based cross-sectional study was carried out in postnatal and Child Welfare Clinics (CWC) in Ga East district from May to July 2015. Quantitative data were collected from 220 randomly selected first time mothers attending CWC, by self-administered questionnaire and interviewer-administered based on literacy status. Chi-square analyses were used to identify factors associated with timely breastfeeding initiation. Multiple logistic regression analyses identified the independent factors associated with timely breastfeeding initiation. RESULTS: A total of 48.2% first time mothers initiated timely breastfeeding at birth compared to 51.8% who did not initiate breastfeeding. A total of 34.1% mothers’ gave prelacteal foods to their children the first few days after birth. More mothers between the ages 21 to 30 reported giving prelacteal food (76%). Mothers who initiated breastfeeding within one hour were less likely to use any prelacteal food (AOR=0.25, 95% CI 0.14-0.46, Pvalue <0.0001) compared to mothers who did not initiate breastfeeding at birth. Also mothers who practiced prelacteal feeding were 2.1 times more likely to give water before the child is six months (OR=2.1, 95% CI 0.98-4.4, Pvalue <0.0001) compared to those who did not practice prelacteal feeding. The factors that were significant in predicting timely breastfeeding initiation were prelacteal feeding (AOR=0.25, 95% CI 0.14-0.46, Pvalue <0.0001), obstetric outcome (AOR=0.43, 95% CI 0.24-0.77, Pvalue 0.005) and maternal intention to breastfeed exclusively (OR=0.36, 95% CI 0.20-0.64, Pvalue 0.001). CONCLUSION: Timely breastfeeding initiation rates among first time mothers were low (48.2%) but similar to general population of mothers in Ghana (45.9%). There is a need to focus strategies in improving optimal breastfeeding early among first time mothers.
Thesis (MPH) - University of Ghana, 2015